2012
DOI: 10.1002/jctb.3765
|View full text |Cite
|
Sign up to set email alerts
|

Axonopus compressus (Sw.) P. Beauv. A native grass species for phytoremediation of hydrocarbon‐contaminated soil in Assam, India

Abstract: BACKGROUND: The aim of this study was to assess the suitability of Axonopus compressus for the removal of petroleum hydrocarbons from contaminated soil. An experiment was conducted with crude oil contaminated soil to evaluate the degradation of this crude oil in pots in the presence of A. compressus for 360 days. Study of the degradation of total petroleum hydrocarbon (TPH), its accumulation in roots and shoots, plant growth and biomass production and most probable number (MPN) was conducted at 60 day interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
(36 reference statements)
2
16
0
Order By: Relevance
“…After 14 days, the lawn is fertilized in order to speed up the grass growth. On day 30, the grass is removed and the length of the root length is Referring to previous studies, on day 30, the length of the roots of Cow Grass is 5cm [8]. The length of Cow Grass roots that planted in sandy loam soil in this previous study is similar to the growth of the grass on laterite soils.…”
Section: Observation On Cow Grass Growthsupporting
confidence: 65%
See 2 more Smart Citations
“…After 14 days, the lawn is fertilized in order to speed up the grass growth. On day 30, the grass is removed and the length of the root length is Referring to previous studies, on day 30, the length of the roots of Cow Grass is 5cm [8]. The length of Cow Grass roots that planted in sandy loam soil in this previous study is similar to the growth of the grass on laterite soils.…”
Section: Observation On Cow Grass Growthsupporting
confidence: 65%
“…The length of the root measure and observe in 360 days. The growth of root at the end of this experiment of the previous study is 35cm [8].…”
Section: Observation On the Growth Of Cow Grassmentioning
confidence: 84%
See 1 more Smart Citation
“…This finding agrees the previous works of Bordoloi et al . 21 who have reported about the efficiency of Axonopus compressus for removal of oil and grease from the crude oil-contaminated soil. Similarly, Basumatary et al .…”
Section: Discussionmentioning
confidence: 99%
“…Bordoloi et al [12] grew Axonopus compressus for 360 days in oil-contaminated soils and found that the addition of fertilizer enhanced both plant growth and remediation effects; the TPH level was reduced by 70% in fertilized soils compared to a 40% reduction in unfertilized-soils. Therefore, these results indicate that optimizing soil fertility by applying fertilizer also may enhance phytoremediation effects.…”
Section: Introductionmentioning
confidence: 99%